The Vomer Bone Pattern Variations in Dentofacial Discrepancy using three-dimensional Analysis - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Objectives: Objective: The aim of this study was to evaluate the spatial and dimensional morphometric changes of the vomer bone in relation to the mid face deficiency. Methods: The CBCT images of 96 patients in Marmara University / Faculty of Dentistry/Orthodontic department patients cases archive were there images evaluated within age between 16 to 30 years old, with normal occlusion and Angle Class III malocclusion. Patients CBCT images analyzed with Steiner analysis using linear and angular reference planes of 13 skeletal points selected. The 3D reconstructive models of vomer bone dimension were built and measured using MIMICS 19.0V software and all data analyzed statistically Results: There was a statistically significant relationship in both linear and angular measurements of the vomer bone where the anterior values (p < 0.01) and the posterior value of (P < 0.05). Also the correlation was highly significant (p < 0.01) in males and severe (type C) group of mid-face insufficiency. The 3D reconstructive models of vomer bone appeared wider and longer in dimensions when they measured in the severe (type C) group to be statistically different from other groups (p < 0.01). Conclusion: The results of this study found the active role of vomer bone in mid-face region in all planes and its effect on Mid-face malocclusion.
Keywords: MIMICS; Orthodontics; Vomer Bone; Mid-Face Deficiency; NASAL-SEPTUM; ANATOMICAL VARIATION; TERM; STABILITY; MACHINE